2021
DOI: 10.1002/oby.23127
|View full text |Cite
|
Sign up to set email alerts
|

Multiomic Predictors of Short‐Term Weight Loss and Clinical Outcomes During a Behavioral‐Based Weight Loss Intervention

Abstract: Objective Identifying predictors of weight loss and clinical outcomes may increase understanding of individual variability in weight loss response. We hypothesized that baseline multiomic features, including DNA methylation (DNAme), metabolomics, and gut microbiome, would be predictive of short‐term changes in body weight and other clinical outcomes within a comprehensive weight loss intervention. Methods Healthy adults with overweight or obesity (n = 62, age 18‐55 years, BMI 27‐45 kg/m2, 75.8% female) partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…However, other studies have shown inconsistent relationships between Phascolarctobacterium and markers of insulin sensitivity (as discussed in Naderpoor et al, 2019). In this study, as well as in a prior multi-omic study using this same cohort, higher Lachnospiraceae other abundance at baseline was associated with less reduction in waist circumference [ 23 ], yet we also observed that an increase from baseline to three months in this taxon was actually associated with greater weight loss among DCR participants. This is a heterogeneous group with potentially diverse functional effects, and these associations should be further explored, ideally using shotgun metagenomic sequencing data to resolve species/strain-level taxonomy.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, other studies have shown inconsistent relationships between Phascolarctobacterium and markers of insulin sensitivity (as discussed in Naderpoor et al, 2019). In this study, as well as in a prior multi-omic study using this same cohort, higher Lachnospiraceae other abundance at baseline was associated with less reduction in waist circumference [ 23 ], yet we also observed that an increase from baseline to three months in this taxon was actually associated with greater weight loss among DCR participants. This is a heterogeneous group with potentially diverse functional effects, and these associations should be further explored, ideally using shotgun metagenomic sequencing data to resolve species/strain-level taxonomy.…”
Section: Discussionsupporting
confidence: 70%
“…The data for this ancillary study includes information collected at baseline and three months into the intervention for the participants who provided a fecal sample at one of these study visits. As described previously [ 23 ], all participants in the parent trial receive a 12 month comprehensive behavioral weight loss intervention involving an energy-restricted diet, increased physical activity, and group-based behavioral support. Participants are randomized to focus on either IMF or DCR as the dietary strategy during the 12 month intervention.…”
Section: Methodsmentioning
confidence: 99%
“…All study procedures were approved by the Colorado Multiple Institutional Review Board, and participants provided written informed consent. Details regarding inclusion and exclusion criteria and complete study procedures have been published previously [16, 17].…”
Section: Methodsmentioning
confidence: 99%
“…Details regarding inclusion and exclusion criteria and complete study procedures have been published previously [16,17]. Daily intake of energy, macronutrients, fiber, micronutrients, and food-group serving counts were exported from NDSR, and mean intakes over the 7 days were calculated.…”
Section: Study Importancementioning
confidence: 99%
“…For instance, the abundance of Subdoligranulum species was associated with more significant weight loss only after IF intervention (64). A short-term weight loss intervention based on a CRD reducing caloric intake by 34% showed improved weight reduction linked to Coprococcus species baseline abundance, while Bacteroides and Lachnospiraceae species were negatively related to waist circumference reduction (65).…”
Section: Frontiers In Nutritionmentioning
confidence: 99%